A dynamic panel threshold model to analyse The investment-growth nexus on a sample of advanced economies, emerging markets and developing countries - Ribeiro, António Pinto (2017)
This paper studies the Investment-Growth nexus, resorting to a Dynamic Panel Threshold model, for a sample of 12 Advanced, Emerging Markets and Developing Economies. The model estimated a 2.042% and 7.603% inflation threshold for Advanced Economies and for the Emerging Markets and Developing Economies, respectively. The impact of investment on GDP growth is significant and positive for Emerging Markets and Developing Economies in both inflation regimes, whereas for Advanced Economies positive significance is only observed when inflation is above the threshold.